Antibacterial and Antiallergic Effects of Three Tea Extracts on Histamine-Induced Dermatitis - Zeting Huang; Lanyue Zhang; Jie Xuan; Tiantian Zhao; Weihua Peng (MDPI AG, 2024)
Atopic dermatitis (AD) is a persistent and recurrent inflammatory skin condition with a genetic basis. However, the fundamental reasons and mechanisms behind this phenomenon remain incompletely understood. While tea extracts are known to reduce histamine-induced skin allergies and inflammation, the specific mechanisms by which various types of Chinese tea provide their protective effects are still not fully elucidated. In this study, a model of skin itching induced by histamine is used to explore the functions and mechanisms of three types of tea extract (Keemun black tea (HC), Hangzhou green tea (LC), and Fujian white tea (BC)) in alleviating histamine-induced dermatitis. The components of three tea extracts are identified by UPLC-Q-TOF-MS, and we found that their main components are alkaloids, fatty acyls, flavonoids, organic acids, and phenols. The inhibitory effects of three types of tea extract on Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) in skin injury are investigated by MIC and flow cytometry. The three types of tea extract have an inhibitory effect on the growth of bacterial flora, with HC showing the best inhibitory activity. The effect of the three types of tea extract on histamine-induced dermatitis is also evaluated. Furthermore, itchy skin experiments, HE staining, toluidine blue staining, and immunohistochemical staining of mouse skin tissues were performed to determine the variations of scratching, epidermal thickness, mast cell number, IL-1β, and NGF content after the administration of the tea extracts. The three types of tea extracts all alleviate and inhibit skin itching, epidermal hyperplasia, and allergic dermatitis. BC effectively alleviates epidermal hyperplasia caused by skin allergies, and LC significantly downregulates NGF. HC reduces histamine-induced mast cell infiltration and downregulates IL-1β to alleviate skin itching. Consequently, tea emerges a potent natural product that can inhibit the growth of skin wound bacterial flora and exhibit skin repair effects on histamine-induced allergic dermatitis.